Engagement And Customer Satisfaction Behaviour Model Increasing Repurchase Intention In The Health Services Industry In Jakarta - Jatmiko, Jatmiko; Sugiyanto, Sugiyanto; Putra, Adrie; Tamzil, Fachmi (UI Scholars Hub, 2023)
Manuscript Type: Research Article. Research Aims: Testing the influence of E-Service Quality, Customer Engagement and Perceived Quality on Repurchase Intention through Customer Satisfaction in the health services industry in Jakarta, in order to develop a marketing strategy based on customer satisfaction. Design/Methodology/Approach: Data was collected through an online survey from 150 outpatients who were at least 17 years old and had undergone inpatient treatment once a year in 2023, or underwent outpatient treatment once in the last 6 months. Data was analyzed via PET Analysis. Research Findings: E-service quality, customer involvement, and perceived quality positively influence repurchase intention by enhancing customer satisfaction, as indicated by research results. To boost repurchase interest in the health services sector, the hospital medical staff needs to provide customer satisfaction, leading to increased likelihood of repurchasing and recommending to others. Theoreticial Contribution/Originality: E-service quality, engagement, and customer satisfaction positively influence repurchase intentions. Therefore, practitioners and policy makers should prioritize enhancing these factors to boost corporate performance. Practitioner/Policy Implication: The health services industry in Jakarta must increase customer satisfaction through improving Electronic Service Quality (E-Service Quality), customer engagement and perceived quality. Furthermore, at the policy maker level, they must prioritize improving these factors to improve company performance. Research Limitation/Implications: Sample size, quantitative methods need to be developed to include other factors that determine purchase intention such as price and brand. Keywords: E-Service Quality, Customer Engagement, Perceived Quality, Customer Satisfaction, Repurchase Intention